Getting the hostages out : who turns the key? - Jenkins, Brian Michael; Rand Corporation (Santa Monica, CA : RAND, 1990)
This paper, an expanded version of an article that appeared in the Los Angeles Times, April 27, 1990, examines the information current at the time about the seven American hostages held in Lebanon. The author discusses the identity and nature of the captors, and then focuses on the degree to which Iran can influence or control them. A corollary issue is the conflict between Iran's need for Western assistance to repair its shattered economy and its aversion to complicity with the West. Bush Administration officials have to chart a difficult course between advocating a no-concessions policy and displaying a willingness to negotiate. The author suggests that the release of the hostages is Iran's problem. While the president personally wants the hostages released and wants to be seen as sensitive and open to all opportunities, the administration feels it can wait. Given the limitations on our knowledge, the many competing priorities and distractions we face in the world, and the grave political risks involved, the administration adheres to its hard-line policy--a prudent and possibly correct approach.
"May 1990."
Cover title.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Hostages -- Lebanon; Iran -- Foreign relations -- United States; Lebanon -- Politics and government -- 1975-1990.; United States -- Foreign relations -- Iran